(untitled) (Biological Sciences - PJSIR, 1995)
Studies on road traffic noise carried out in Karachi city shows that the road traffic noise levels in the city are very high and much beyond the acceptable limits.Therefore, in order to investigate the level of noise contributed by different type of vehicles plying on the city roads and to assess their individual contribution to the high level traffic noise, studies have been carried out on the noise emitted by four types of relatively noisier vehicles as they normally move on the cityroads, The results are discussed with reference to Ly9O’ LyS) and LylO and present existing motor vehicle rules in Pakistan.